'Refugees here and Finns there' – categorisations of race, nationality, and gender in a Finnish classroom. Issue 2 (4th March 2021) - Hummelstedt, Ida; Holm, Gunilla; Sahlström, Fritjof; Zilliacus, Harriet
ABSTRACT: Schools represent a central meeting place where societal inequalities are reproduced and questions of social justice become important. This study focuses on categorisations related to race, nationality, and gender in interactions in Finnish teaching environments, as well as teacher reflections on these situations. We discuss the implications of the categorisations on social justice and the role of the teacher in these situations. We conducted video observations of a sixth-grade teacher in a Finnish primary school. The study employs both critical multicultural education approaches and Conversation Analysis. Results show that the pupils use categories race, nationality, and gender in ways that limit the agency and positioning of some of the pupils. The extensive and intersecting categorisation in teaching situations makes it demanding for teachers to address and challenge unequal norms attached to the categories. Results also indicate that teachers need an understanding of othering and normativity in order to allow spontaneous critical discussion and problematising categorisations that pupils use. Also, the results highlight the importance of involving pupils in the process of questioning norms that do not provide all pupils with the same agency or sense of belonging.